442. Common symptoms of outpatient COVID-19 compared to non-COVID-19 Cases: A prospective epidemiologic study in a major US metropolitan area. (31st December 2020) - Fairley, Jessica K; Taibl, Kaitlin R; Landay, Taylor; Sherman, Amy C; Wu, Henry M; Collins, Matthew H
Abstract: Background: The majority of novel coronavirus 2019 (COVID-19) cases is comprised of non-critically ill adults. However, the medical epidemiology and clinical profile for mild COVID-19 is poorly described in the United States. Methods: We prospectively recruited 151 mildly symptomatic adults from Emory Healthcare COVID-19 screening clinics in Atlanta, Georgia from March 18 to June 16, 2020. Interview-based questionnaires captured participants' demographics, epidemiological history, and clinical features. Nasopharyngeal swabs were collected to test for SARS-CoV-2 by RT-PCR. Convalescent serum (13–74 days post symptom onset) from 19 participants was tested by an IgG ELISA. Descriptive and χ 2 analyses were performed to determine the characteristics of COVID-19 cases compared to patients who tested negative. Results: A total of 151 patients were recruited. The majority were non-Hispanic white (51%), female (60%), middle-aged adults (46.3 y +/-15). Twenty-seven (17.9%) tested positive for SARS-CoV-2 and most frequently reported fever (63%), cough (67%), fatigue (56%), and myalgias (56%). See Table 1. Fever was statistically more common in positive cases vs negative (63% vs 34%, p = 0.005). Cases also experienced loss of taste (22%) and loss of smell (19%) more frequently than non-cases (p=0.01 and p=0.03). Diarrhea (22% vs 23%) and shortness of breath (33% vs 36%) did not differ significantly between groups. None of the 14 PCR-negative participants tested positive for SARS-CoV-2-specific IgG and 3 out of 5 COVID-19 cases tested positive for SARs-CoV-2-specific IgG. Conclusion: Mild COVID-19 cases reported fever, loss of smell and loss of taste significantly more than non-COVID-19 cases. Strong correlations between anosmia and ageusia with COVID-19 have been reported elsewhere, however these symptoms were only present in 19–22% of cases at the time of testing, limiting their utility for clinical diagnosis. Also, none of the PCR-negative participants tested positive for convalescent serology, supporting good sensitivity and negative predictive value of the RT-PCR test used in our clinic. Symptoms alone cannot differentiate COVID-19 from other illnesses, highlighting the critical need for widely available and highly sensitive and specific diagnostic tests. Disclosures: All Authors : No reported disclosures